Evaluation of ethical attitude approaches in midwives and their relationship with their demographic features - Narges Afhami; Nafisehsadat Nekuei; Parvin Bahadoran; HamidReza Taleghani-Esfahani (Wolters Kluwer Medknow Publications, 2018)
Background: Ethical approach is one of the paramount aspects of life. The position of this approach in medical occupations has always been noticed. This study was carried out to analyze the types of ethical approaches in midwives and their relationship with their demographic features. Materials and Methods: The current descriptive-correlation and cross-sectional study was conducted from October to December 2014 using quota random sampling technique. The participants consisted of 189 midwives employed in Isfahan, Iran. The data collection tool was a researcher-made questionnaire. The midwives' attitudes were examined in the four fields of virtue ethics, deontologism, utilitarianism, and religious ethics. Data were analyzed using descriptive and inferential statistics in SPSS software (p < 0.050). Results: The highest score belonged to religious ethics with the mean value of 64.36 out of 100. A positive significant relationship was found between deontologism and education level (F = 8.74; p = 0.004), and total ethical approach and workplace (F = 2.60; p = 0.053). There was a reverse significant relationship between age and work experience and virtue ethics (r = −0.15; p = 0.035 and r = −0.20; p = 0.005, respectively). Conclusions: The existing high percentage of religious ethics shows the religious tendency of the participants. The determination of ethical approach among midwives as one of the important medical groups and creation and improvement of the most appropriate attitude among them based on the present regulations and requirements in society are principles that we should attempt to achieve.